Student Errors Analysis Problem-Solving based Castolan Theory on Relations and Functions Material - Reskina; Sehatta Saragih; Elfis Suanto; Maimunah (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
Material relations and functions load understanding concept on lesson mathematics as well as can help student For finish question mathematics with good and right. Objective study This is For analyze error student in finish question relations and functions based on theory Castle ie error conceptual, error procedural and error technique as well as reason happening error the. subject study are 18 students class VIII SMPN 13 Dumai. Data collection techniques are carried out with test and interview. Instrument test used is test written from valid questions and guidelines interview For verify reason student in answer question the. Obtained data from results test, then analyzed with use method descriptive qualitative. Analysis results shows 33% students do error conceptual, 41% students do error procedural, and as many as 26% students do error technical. As for what causes students are wrong finish question Relations and functions including : 1) less understand cause issue student Confused finish the answer ; 2) no control rule calculation algebra ; 3) rush in finish question so that lots wrong calculation.